2021
DOI: 10.1177/17455065211061969
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and fetal characteristics to predict c-section delivery: A scoring system for pregnant women

Abstract: Introduction: Cesarean section is one of the most common obstetrical interventions that has been performed at an increasing rate globally, due to both medical and non-medical reasons. This study aims to develop a prediction tool for pregnant women potentially needing c-section, such that necessary preparations from the mothers, families, and health providers can be made. Methods: A total of 603 pregnant women were recruited in the first phase of c-section prediction tool development. The association between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 30 publications
2
6
0
Order By: Relevance
“…As it was a cross sectional study hence the study participants were matched for age. There are recent studies which show that the incidence of C-section among pregnant ladies is on a rise generally in the world as those studies show the benefits of a planned C-Section (9). In contrast we cannot take history of the study participants that whether they had planned C-section or it was done as an emergency measure.…”
Section: Discussionmentioning
confidence: 91%
“…As it was a cross sectional study hence the study participants were matched for age. There are recent studies which show that the incidence of C-section among pregnant ladies is on a rise generally in the world as those studies show the benefits of a planned C-Section (9). In contrast we cannot take history of the study participants that whether they had planned C-section or it was done as an emergency measure.…”
Section: Discussionmentioning
confidence: 91%
“…This study also showed that, women who had history of fistula were more likely to give birth by emergency caesarean delivery as compared to women who had no history of fistulas. A previous study also suggested that obstetric complications increase the risk of emergency caesarean delivery [ 10 ]. This might be associated with the fact that women with a history of fistulas may face a problem of failure in labour progress because of prolonged and obstructed labour.…”
Section: Discussionmentioning
confidence: 99%
“…But specifically, the magnitude of emergency caesarean delivery and its predictors are not well addressed in Ethiopia. In developing countries, including Ethiopia, lack of knowledge about childbirth-related complications, delays in referrals, and resource-limited health care systems, including the low access to emergency caesarean delivery, are highly correlated with maternal and fetal health [ 10 ]. In Ethiopia, access to emergency caesarean delivery is available only at hospitals and specialty clinics [ 11 , 12 ], and still the birth-related complications and deaths are high [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…From the overall data sets that comprised over 200 columns, only a few columns were selected (see Table 1 ). We used a mixture of features selected by surveying the literature [ 21 - 23 ] and features with a high correlation with the outcome. The tested models were logistic regression, decision tree, random forest, 3 different boosting methods (as implemented by extreme gradient boosting [XGBoost], light gradient-boosting machine [LightGBM], and scikit learn), and a linear model based on stochastic gradient descent.…”
Section: Methodsmentioning
confidence: 99%